Myxedema coma precipitated by diabetic ketoacidosis after total thyroidectomy: a case report - Jin Joo Kim; Eun Young Kim (Journal of Medical Case Reports, 2019)
Abstract Background Myxedema coma is profound decompensated hypothyroidism usually precipitated by stressors, and its occurrence in association with total thyroidectomy or metabolic disorders, such as diabetic ketoacidosis, is unusual. Case presentation A 43-year-old Asian man with history of total thyroidectomy who was scheduled for a second radioactive iodine therapy presented to our hospital with decreased mental status and hyperglycemia. He had a history of thyroid cancer but did not have diabetes mellitus. He was in a hypothermic state and had a Glasgow Coma Scale score of 10 out of 15 at presentation; arterial blood gas analysis revealed a state of metabolic acidosis and laboratory findings suggested hyperglycemia with glycosuria, ketoacidosis, and severe hypothyroidism. A thyroid function test showed thyroid-stimulating hormone of 34.126 uIU/mL, free thyroxine of 1.02 ng/dL, and triiodothyronine of 1.04 ng/mL. The glycated hemoglobin of this patient was checked due to hyperglycemia and the value of glycated hemoglobin was 16.5% which met the criteria for a diagnosis of diabetes. After treatment for myxedema with liothyronine 5 mcg two times per day and levothyroxine 175 mcg once daily via a nasogastric tube and diabetic ketoacidosis with intravenously administered fluid and insulin, his clinical condition rapidly improved including mental status, hyperglycemia, and acidosis. During the hospitalization, a workup for diabetes mellitus was performed and the results suggested that a diagnosis of type 2 diabetes mellitus would be appropriate. Conclusions This case demonstrated that diabetic ketoacidosis not only could be a potential contributor to myxedema coma but also mask typical clinical features, making diagnosis more difficult. Considering the possibility of an increasing number of potential patients with hypothyroidism developed after thyroidectomy, constant vigilance is required for a better clinical outcome, including early recognition and management in critical care in advance for unusual diabetic ketoacidosis which could precipitate decompensated hypothyroidism.